Catalytic Performance of Preyssler Anion in Selective Oximation of Aromatic Aldehydes - F. BAMOHARRAM, FATEMEH; M HERAVI, MAJID; ROSHANI, MINA; SH. EMAMPOUR, JALAL; RASHKI, NASRIN (Asian Journal of Chemistry, 2010)
Preyssler catalyst, H14[NaP5W30O110], catalyzes the aldoximation of aromatic aldehydes for the synthesis of Z-isomers in conventional manner and under microwave irradiation. Both pure acid and silicasupported catalysts were used and their activities compared with common catalysts such as K2CO3 and CuSO4. The Preyssler is the catalyst for this reaction.